Awareness Status of Stroke among the Students of Saraswati Multiple Campus: An Exploratory Study - Adhikari, Anup; Adhikari, Ashmita; Malla, Supriya (Nepal Journal of Multidisciplinary Research, 2023)
Stroke is a cerebrovascular disease characterized as a medical emergency that occurs when a blockage ensues in the brain and the blood supply is interrupted or discontinued by any means. It is popularly categorized as Ischemic stroke, Intracranial Hemorrhage, and Subarachnoid Hemorrhage and is one of the leading cause of deaths worldwide. This research includes prevention techniques, treatment strategies, opinions, and the awareness status of respondents, sequentially including the citations of various researchers on the issue of stroke. The research explores stroke-associated factors and the awareness status among the students, who are currently pursuing the degree, Master of Arts in Sociology and English at Saraswati Multiple Campus, Tribhuvan University. Similarly, the number of respondents was 22, and the data was collected through a convenience sampling technique that demonstrates the opinions of the respondents. The researcher has used both qualitative and quantitative methods to analyze the data. The principal findings present that the respondents (40.91%) believes hypertension is the major factor in stroke, whereas respondents (54.5%) agrees that exercise and healthy lifestyle modification can reduce the risk factors. Correspondingly, the data concludes respondents (86.4%) takes the stroke patient to the hospital and shows the overall awareness status is satisfactory. Furthermore, the knowledge in the event of stroke contribution to the patient is strong and the respondents (77.3%) have stated that the stroke affects the brain, although they are not familiar with Cardiopulmonary Resuscitation (CPR) techniques if the patient is in unconscious condition having breathing problem. Finally, the research concludes that stroke awareness status is satisfactory among the respondents and prioritizes that stroke-related course books must be included at the University level of Social Sciences disciplines, whereby the proper information and knowledge spreads within the students. It improves on identifying the actual symptoms and also encourages the patient's early admission to the hospital, which helps to decrease disability and other impairments via conducting proper methods.